One century of Karl Jaspers' general psychopathology - Stanghellini, Giovanni; Fuchs, Thomas ([International perspectives in philosophy and psychiatry], 2013)
2013 sees the centenary of Jaspers' foundation of psychopathology as a science with the publication of his magnum opus the 'Allgemeine Psychopathologie' ('General Psychopathology'). Many of the issues concerning methodology and diagnosis are today the subject of much discussion and debate. This volume brings together leading psychiatrists and philosophers to discuss the impact of this volume, its relevance today, and the legacy it left.